Four Element MIMO Antenna Systems with Decoupling Lines for High-Speed 5G Wireless Data Communication - Imaculate Rosaline; Arvind Kumar; Prashant Upadhyay; Abu Hena Murshed (International Journal of Antennas and Propagation)
A low-profile planar multiple-input multiple-output (MIMO) antenna consisting of four elements with isolation improvement is proposed for 5G mm Wave (24–40) GHz applications. Each radiating element of the MIMO antenna comprises of a microstrip-fed tilted spade-shaped radiator with four asymmetrical slots and a partial ground plane. The antenna is optimized to resonate at 35 GHz covering a wide impedance bandwidth from 23.9 to 40.1 GHz. Two cross lines are then loaded between the antenna elements to improve the isolation >−30  dB. The MIMO structure with the decoupling lines is fabricated and tested. The measured results are in good correlation with the simulated results. Other MIMO performance metrics such as the envelope correlation coeﬃcient (ECC), channel capacity loss (CCL), diversity gain (DG), and total active reflection coefficient (TARC) are examined, and the results are found to be satisfactory for the device to be used for mm-wave 5G MIMO applications. Also, the antenna’s performance metrics such as radiation efficiency, gain, and radiation patterns over the operating band are presented.